Ectopic Intralaryngo-Tracheal Thyroid Tissue Causing Neonatal Death. (3rd September 2017) - Furnas, Lauren; Safa, Huda; Hutchinson, Fiona; Joseph, Lindsay; Armes, Jane E.
ABSTRACT: Introduction : Ectopic thyroid tissue can be found anywhere along the embryologic path of thyroid descent. Intralaryngo-tracheal thyroid tissue is the least common site of ectopia and can present with upper airways obstruction. Its presentation in the neonate is exceptional. Case Report : We describe a term female neonate with subglottic thyroid tissue causing near-total occlusion of the larynx, which led to upper airways obstruction and neonatal death. Conclusion : This emphasizes the importance of considering intralaryngo-tracheal tumors as a cause of acute and otherwise unexplainable respiratory distress immediately after birth. The cause of this neonatal death would not have been elucidated without careful autopsy examination.